A comprehensive evaluation of the non gray gas thermal radiation using the line-by-line model in one- and two-dimensional enclosures. (September 2017) - Chu, Huaqiang; Ren, Fei; Feng, Yan; Gu, Mingyan; Zheng, Shu
Highlights: A line-by-line model with HITEMP2010 database was comprehensively investigated. The effect of four factors on radiation were accounted for in the line-by-line model. The total pressure from 1 to 10 atm significantly enhanced thermal radiation. The results calculated using SNB and SNBCK models were also given as comparisons. Abstract: In oxy-fuel combustion with CO2 recycle, the non-gray gas radiative heat transfer characteristics of gaseous participating media are different from those in air-fuel combustion. Water and carbon dioxide are the most important gas products of combustion under O2 /CO2 atmosphere. A line-by-line model with HITEMP2010 database was comprehensively investigated in one- and two-dimensional enclosures containing H2 O/CO2 /N2 in this study. The radiative transfer equation was solved using the discrete ordinates method. The thermal radiation characteristics of water and carbon dioxide were determined numerically per their non gray radiative characteristics. The line-by-line model, statistical narrow band model, and statistical narrow band correlation-k model were used to run the calculations. The effect of four factors on radiation were accounted for in the line-by-line model: Spectral line resolution, spatial discretization scheme, quadrature, and total pressure. The calculation results showed that spectral line resolution, which varied from 0.02 to 0.08 cm −1, has a significant impact on computing time. The total pressure was the most influential factor overall, however. Increase in total pressure from 1 to 10 atm significantly enhanced thermal radiation in regards to the magnitude of the local radiative source term.